Impact of Platoon Size on the Performance of TDMA-Based MAC Protocols - Aslam, Aqsa (2018)
Vehicular networks are a core component in Intelligent Transportation Systems (ITS) enabling communication among vehicles for collaborative applications. One example of such an application that may bring benefits in reducing travel time, fuel consumption and improving safety is platooning. This application coordinates a group of vehicles that travel together, doing automatic control of inter-distances and speeds [1]. A critical part of this application is the vehicle-to-vehicle (V2V) communication highlighting the importance of improving the channel quality. Existing ITS standards, namely WAVE (USA) and ITS-G5 (Europe), use IEEE 802.11p DSRC (Dedicated Short-Range Communication) [2] that relies on CSMA/CA distributed access arbitration. Despite the Collision Avoidance attribute collisions can still occur and the channel quality can degrade significantly in dense traffic environments.